On the mechanical biocompatibility of Ti-15Zr-based alloys for potential use as load-bearing implants - Correa, D. R.N.; Rocha, L. A. [UNESP]; Donato, T. A.G. [UNESP]; Sousa, K. S.J. [UNESP]; Grandini, C. R. [UNESP]; Afonso, C. R.M.; Doi, H.; Tsutsumi, Y.; Hanawa, T. (Elsevier, 2020)
This study evaluated the mechanical properties and cytocompatibility of recently developed Ti-15Zr-based alloys with Mo addition for potential use as load-bearing implants. The phase composition and microstructure were changed by the alloying elements, being the β phase fully retained on the Ti-15Zr-10Mo and Ti-15Zr-15Mo samples. The TEM analysis showed that a small quantity of ω phase was precipitated on the samples with a high amount of Mo. Regarding the mechanical properties, the Ti-15Zr-10Mo sample presented high mechanical strength and large elongation (854»±»63»MPa and 18.7»±»2.8 %). However, the Ti-15Zr-15Mo sample exhibited better mechanical compatibility, due to its combination of low Young's modulus (75»±»1»GPa) and high Vickers microhardness (346»±»4»HV). Some dimple-type structures found along the fractured surface confirmed the ductile behavior of these samples. The MTT test indicated non-cytotoxic effects of all samples when in contact with osteoblastic cells (p»<»0.05). The wettability values of the samples were adequate for biomedical applications. The mechanical properties of the Ti-15Zr-15Mo sample were better than some commercial metallic biomaterials, which highlights its great potential for use as load-bearing implants.
Keywords: Biomaterial; Load-Bearing implant; Mechanical properties; Ti-Zr-Mo alloy